NanoFab SIMS: High Spatial Resolution Imaging and Analysis Using Inert-Gas Ion Beams. (May 2019) - Sijbrandij, Sybren; Lombardi, Alexander; Sireuil, Alain; Khanom, Fouzia; Lewis, Brett; Guillermier, Christelle; Runt, Doug; Notte, John
Abstract: Abstract: By combining a focused inert-gas ion beam instrument and a custom magnetic-sector mass spectrometer, high spatial resolution imaging and chemical analysis are provided within a single instrument. Sub-nanometer image resolution is achieved by secondary electron (SE) imaging, limited only by the probe-size of the primary beam, while the spatial resolution for chemical mapping obtained via secondary ion mass spectrometry (SIMS) is limited mainly by beam-sample interactions to about 10 nm. This article introduces the background behind this development, describes the instrument and its various operating modes, and presents examples of its applications.